Melatonin receptor agonists in neurodegenerative diseases and psychiatric disorders - Dyrek, Nicola; Balwierz, Magdalena; Łata, Marcin; Kosińska, Agnieszka (Quality in Sport, 2024)
Neurodegenerative and psychiatric diseases remain a therapeutic challenge. Mental illnesses such as depression and bipolar affective disorder lead to disruption of the diurnal rhythm of melatonin secretion and disruption of the sleep-wake axis. The use of new melatonergic drugs has received special attention in recent years. Selective melatoninergic M1 and M2 receptor agonists (tasimelteon, ramelteon) show a more favorable metabolic profile, better regulation of circadian rhythms, and effects on total sleep time and sleep quality compared to the already well-studied melatonin. In addition, these drugs show no addictive potential. Agomelatine, through its action on M1 and M2 receptors, as well as serotonergic 5-HT2C and 5-HT2B receptors, exhibits antidepressant, normothymic, and neuroprotective effects, providing primary therapy or adjunctive treatment.